THE ROLE OF INFORMATION TECHNOLOGIES IN THE DEVELOPMENT OF A MODERN EDUCATION SYSTEM (Scientific journal of the Fergana State University, 2024)
In this article, we are talking about the fact that today computer technologies have widely penetrated into the field of modern education, as well as in other areas, and this is not important in improving the effectiveness of the educational process and increasing the overall intellectual potential, and life today is impossible to imagine without information media and the Internet. The information on the reform of the education system in the conditions of independence of Uzbekistan is highlighted, first of all, the introduction of advanced information technologies into the education and training system.